2016
DOI: 10.5966/sctm.2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Directing Differentiation of Pluripotent Stem Cells Toward Retinal Pigment Epithelium Lineage

Abstract: Development of efficient and reproducible conditions for directed differentiation of pluripotent stem cells into specific cell types is important not only to understand early human development but also to enable more practical applications, such as in vitro disease modeling, drug discovery, and cell therapies. The differentiation of stem cells to retinal pigment epithelium (RPE) in particular holds promise as a source of cells for therapeutic replacement in age‐related macular degeneration. Here we show develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Human pluripotent stem cells have the potential to assist in the identification of genes associated with �a��alian develo�� genes associated with mammalian develop-s associated with mammalian develop-mammalian development (1,2), and the plasticity of stem cells suggests that they may have a wide range of clinical applications (3,4). Bone tissue engineering has also been explored for clinical purposes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Human pluripotent stem cells have the potential to assist in the identification of genes associated with �a��alian develo�� genes associated with mammalian develop-s associated with mammalian develop-mammalian development (1,2), and the plasticity of stem cells suggests that they may have a wide range of clinical applications (3,4). Bone tissue engineering has also been explored for clinical purposes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated purity by combined image analysis of pigmentation together with staining for several intracellular markers 28 . However, global transcriptional analysis has revealed that contaminants of cells with alternative fate can be found, such as lense-like cells expressing genes encoding crystallins in <10% of otherwise apparently homogeneous cultures 29 . Such contaminants may be difficult to identify by image analysis for pigmentation and intracellular staining of RPE markers.…”
Section: Discussionmentioning
confidence: 99%
“…This hurdle was overcome in 2012 by using human fibroblast feeder cells [103] as opposed to non-human feeder cells, and later by methods obviating the need for feeder cells [104]. Differentiation of desired cells is a time-consuming process, and from 2013-2016, numerous investigators have published successively more efficient methods of RPE differentiation [105][106][107][108][109][110][111].…”
Section: Preclinical Stem-cell Based Retinal Pigment Epithelium Studiesmentioning
confidence: 99%